2019
DOI: 10.3390/w11081734
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Changes in Flood Data in Australia

Abstract: This study performs a simultaneous evaluation of gradual and abrupt changes in Australian annual maximum (AM) flood data using a modified Mann–Kendall and Pettitt change-point detection test. The results show that AM flood data in eastern Australia is dominated by downward trends. Depending on the significance level and study period under consideration, about 8% to 33% of stations are characterised by significant trends, where over 85% of detected significant trends are downward. Furthermore, the change-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…Severe flooding episodes are expected to occur between 25% and 30% more quickly considering an increment tendency of 12% for the 20-year return values expected by CMPI5 CC modelling under an RCP4.5 radiative scenario. These results show an important regional increasing trend in the future local precipitations, which contrasts with that recently reported by Ishak and Rahman [90], Ishak et al [91], who found regional decreasing trends in annual maximum floods in Australia. Results also allow projecting policies to increase Tamuín city resilience to flood, as well as to better draw local civil protection plans.…”
Section: Discussioncontrasting
confidence: 99%
“…Severe flooding episodes are expected to occur between 25% and 30% more quickly considering an increment tendency of 12% for the 20-year return values expected by CMPI5 CC modelling under an RCP4.5 radiative scenario. These results show an important regional increasing trend in the future local precipitations, which contrasts with that recently reported by Ishak and Rahman [90], Ishak et al [91], who found regional decreasing trends in annual maximum floods in Australia. Results also allow projecting policies to increase Tamuín city resilience to flood, as well as to better draw local civil protection plans.…”
Section: Discussioncontrasting
confidence: 99%
“…In the USA, mixed changes have been found for central and eastern regions; clearer patterns of decreasing floods have been detected in the western USA, particularly in California, in line with decreases in precipitation and catchment wetness [151][152][153][154][155][156] . In other regions of the world, decreasing trends in annual maxi mum flows have been found in northeast Brazil 157 and southeast Australia 158 as well as in China 159 and India 156 . There are also a number of regions with increasing trends such as the south of Brazil 157 and the north of Australia 158 .…”
Section: Observed Trendsmentioning
confidence: 99%
“…In other regions of the world, decreasing trends in annual maxi mum flows have been found in northeast Brazil 157 and southeast Australia 158 as well as in China 159 and India 156 . There are also a number of regions with increasing trends such as the south of Brazil 157 and the north of Australia 158 .…”
Section: Observed Trendsmentioning
confidence: 99%
“…The limitation of using these approaches (whether FFA or RFFA) is that the requirement of a reasonably long period of flow observations collected at or (at least) close to the site of interest. Additionally, these approaches assume that the flow data are stationary over time, which may not always be the case especially in the context of climate change and land use changes (Ishak and Rahman 2019).…”
Section: Introductionmentioning
confidence: 99%